Primary health care as assessed by health professionals: comparison of the traditional model versus the Family Health Strategy - Cristina Rabelo Flôr; Cláudia Di Lorenzo Oliveira; Clareci Silva Cardoso; Cleonice Ferreira Rabelo; Bernardo Luis Gontijo; Suzana Freitas de Carvalho; Pedro Messenger Caldeira Bretas; Hygor Cabral Silva; Mariana Linhares Pereira; Cristiane Menezes de Pádua
ABSTRACT: Introduction: The Family Health Strategy (FHS) should be first-contact care in the Brazilian Health System. However, Primary Health Care (PHC) still encompasses two models: the FHS and the traditional health care facilities. The expansion of the FHS has been slow and heterogeneous in many cities, rendering a comparative evaluation of key quality-related elements of PHC models crucial. Objective: To compare the performance of PHC models as perceived by health professionals. Methods: A cross-sectional study involving managers and health professionals from PHC of a medium-size city in South-eastern Brazil. Data were collected by applying the Primary Care Assessment Tool. The performance was estimated through primary health care indexes (general and partial PHCI by attributes). Univariate polytomous logistic regression was performed to compare care model performances according to their attributes. Strength of association was estimated by odds ratio with 95% confidence interval. Results: Three managers and 81 health professionals participated in the study. The FHS had a better index rating than the traditional care model for general PHCI and for the attributes longitudinality, comprehensiveness, family focus and professional level. Conclusion: Although the FHS attained higher scores compared to the traditional model, it has not yet achieved the performance expected. This scenario points to the need for increased FHS cover and quality improvements at the existing units.